Gambaran Coping Stress ASN yang Menjalankan Izin Belajar - Herlambang, Yustisia Donisius; Arianti, Rudangta (Penerbit Goodwood, 2024)
Purpose: This study aimed to comprehensively describe the stress-coping strategies implemented by civil servants (Aparatur Sipil Negara/ASN) aged 40 years and above, focusing on the various cognitive, emotional, and behavioral approaches they employ to manage occupational stress. The research sought to explore how these individuals respond to work-related pressures, administrative demands, interpersonal challenges, and organizational changes, as well as to identify the internal and external resources—such as personal resilience, family support, peer relationships, and institutional support systems—that contribute to their coping processes. Research methodology: This was a qualitative case study. Participants in this study were two civil servants (ASN) in their 40s who were pursuing further education while working. Data collection was conducted through in-depth, semi-structured interviews. Results: The results of this study indicate that both participants used different stress-coping techniques, which were tailored to the unique aspects of each participant, including their economic circumstances and the social environment around them. Conclusions: Both subjects applied positive coping strategies in different but effective ways. Subject H completed their studies, while subject J remains motivated in finishing their final project. Limitations: This study only included married participants consist of individuals from a single ethnic group located in Indonesia. Contribution: This study is expected to provide an overview of the stress-coping strategies of civil servants (ASN) pursuing further education.